Potensi Boron Karbida dengan Doping Serium Oksida sebagai Material Penyerap Gelombang Radar - Mahali, Muhammad Ghufron; Aritonang, Sovian; Muniarti, Riri (Fakultas Teknik UMSU, 2025)
Throughout the history of warfare, the need for hard military equipment could not be replaced even in prehistoric times. Humans mostly used iron helmets or steel armor to protect the human body from attackers. In the era of World War 1, humans created tanks with thick armor and this technology is still widely used. In its development, after the Vietnam war, the need for advanced materials that can absorb radar radio waves to make military equipment undetectable by radar in the current war is very high, this can be seen in many stealth equipment programs such as the joint strikefighter, Nighthawk, Stealth Ship and many more. Departing from this motivation, further discussion is needed about radar-absorbing materials in this case cerium oxide into boron carbide as a material that is not only super hard but also stealth. In this journal, several literatures are processed to hypothesize whether the doping technique of the two materials will become a promising advanced military material without reducing its strength for further experiments. After the literature study, it can be concluded that there are still additional materials to create super hard and stealth materials such as carbon nanofiber.